Potensi Larutan Buah Naga sebagai Alternatif Disclosing Solution dalam Mengukur Indeks Kebersihan Gigi - Jumriani; Asriawal; Asliana , Sri Lely; Liasari, Ira; Priyambodo, R. Ardian (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
This research is motivated by the need to explore more natural alternatives in assessing the level of oral hygiene. Commonly used disclosing solutions often contain chemicals, prompting this study to evaluate the potential of dragon fruit solution as a safer and more economical option. The research aims to compare the effectiveness of dragon fruit solution with disclosing solution in measuring the PHP-M Index among students of the Diploma IV Dental Therapy Program at Poltekkes Kemenkes Makassar. The research method involved 21 subjects who were treated with dragon fruit solution and disclosing solution, and their plaque indices were measured. The results indicated that the dragon fruit solution yielded comparable outcomes to the disclosing solution, with the majority of respondents falling into the 'moderate' criteria. Statistical analysis revealed no significant differences between the two treatments. In conclusion, dragon fruit solution has the potential to replace disclosing solution in measuring the PHP-M Index, offering a natural and affordable alternative. These findings provide a basis for considering more environmentally friendly alternatives in dental hygiene assessment practices. Keywords : Dental plaque; dental hygiene; dragon fruit; disclosing solution